2000
DOI: 10.2337/diabetes.49.3.513
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of serum insulin concentrations to chromosome 3p in Mexican Americans.

Abstract: Hyperinsulinemia predicts the development of type 2 diabetes, and family studies suggest that insulin levels are regulated in part by genes. We conducted a genomewide scan to detect genes influencing variation in fasting serum insulin concentrations in 391 nondiabetic individuals from 10 large multigenerational families. Approximately 380 microsatellite markers with an average spacing of 10 cM were genotyped in all study subjects. Insulin concentrations measured by radioimmunoassay were transformed by their na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…These data are suggestive that abnormalities in the regulation of SLMAP expression in the db/db mouse may be linked to endothelial dysfunction. A single gene that encodes SLMAP maps to the human chromosome 3p14.2-21 region (40, 41), a region that also has been reported to carry genes linked to Type 2 diabetes-related disorders (26). Whether the SLMAP gene locus is involved in these diabetic patients now needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These data are suggestive that abnormalities in the regulation of SLMAP expression in the db/db mouse may be linked to endothelial dysfunction. A single gene that encodes SLMAP maps to the human chromosome 3p14.2-21 region (40, 41), a region that also has been reported to carry genes linked to Type 2 diabetes-related disorders (26). Whether the SLMAP gene locus is involved in these diabetic patients now needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Duggirala et al (24) in 1999 reported a multipoint LOD of 2.56 for diabetes near marker GATA128C02 (Marshfield map, 112 cM) in 440 San Antonio Family Diabetes study participants who were examined at baseline and in 2001 reported a multipoint LOD Ն 1.00 for fasting-specific insulin in 310 nondiabetic San Antonio Family Diabetes study participants at the same locus (38). Moreover, the San Antonio Family Heart Study comprised of a similar study population reports a LOD for serum insulin in 391 nondiabetic individuals of 3.07 on chromosome 3p in the region flanked by D3S1600 (86.0 cM, Marshfield map) and D3S1285 (91.0 cM, Marshfield map) (39). Similar to the SAFDGS, the San Antonio Family Heart study is an extended pedigree study of low-income Mexican Americans in San Antonio, Texas.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies however, the families and participants were collected through an index patient with Type 2 diabetes, and the study cohorts were known to have a higher risk for developing Type 2 diabetes, such as Pima Indians, Mexican Americans and Australian Aborigines. in unaffected individuals three genome scans carried out from such higher risk populations resulted in several candidate regions on chromosome 3 [4,5], chromosome 4 [4], chromosome 9 [4], chromosome 10 [6], chromosome 13 [6], chromosome 17 [6] and chromosome 22 [4]. However, probably due to the complex nature of the disease, failure of replication of postulated genes and false-positive discovery of new loci remains a major concern.…”
mentioning
confidence: 99%